PENGEMBANGAN DAN VALIDASI KUESIONER BELIEF ABOUT MEDICINE (BMQ) UNTUK MENGUKUR PERSEPSI RISIKO MASYARAKAT TERHADAP OBAT SETELAN - Walidah, Ziyana; Hermansyah, Andi; Wijaya, I Nyoman (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Nowadays, the consumption of medicine suits is a problem of self-medication that occurs in the community. BPOM prohibits this medicine from being used, because the quality is not guaranteed and it can cause harm when consumed because it contains several classes of hard drugs. The high consumption of medicine suits indicates a lack of public understanding of the risks posed by medicine suits. Measuring people's perceptions of medicine suits needs to be done, one of which is by filling out a questionnaire. There is no questionnaire that measures a person's perception of suit medicine, so it is necessary to develop research instruments through validity and reliability tests of questionnaires related to measuring people's perceptions or beliefs about a treatment. This study was conducted using observational method and cross sectional time design. Where it involved 30 trial respondents while still paying attention to the inclusion criteria that had been set. The results of this study indicate that the questionnaire designed has met the minimum values of validity and reliability. Where there is only one invalid question item. While in general the resulting value of r count> r table. Regarding reliability, all items have achieved a Cronbach' alpha value of more than 0.6. This indicates that the questionnaire on community risk perception towards legitimate use of medicine suits can be used repeatedly.